Environmental analysis of polar and non-polar Polycyclic Aromatic Compounds in airborne particulate matter, settled dust and soot: Part I: Sampling and sample preparation - Galmiche, Mathieu; Delhomme, Olivier; François, Yannis-Nicolas; Millet, Maurice (TrAC, Trends in analytical chemistry (Regular ed.), 2021)
Interests in Polycyclic Aromatic Hydrocarbons (PAHs) and their derivatives (Nitrated PAHs, Oxygenated PAHs, Azaarenes and Polycyclic Aromatic Sulfur Heterocycles) have been growing because of their toxicity. The first part of this review gathers information on sampling of Polycyclic Aromatic Compounds (PACs) in airborne particulate matter (PM), dust and soot, on their extraction thanks to solvent extraction methods, and on sample clean-up for further analysis. Atmospheric PM is generally sampled on quartz-fiber filters. For settled dust as well as for PM, active samplers are used in most cases. After sampling, solid/liquid extraction is necessary. At this step, yields can be enhanced depending on the device and solvent used, but also with optimization of solvent volume and extraction time. Most up-to-date extraction devices are Pressurized Liquid Extraction (PLE), Ultrasound Assisted Extraction (UAE) and Microwave Assisted Extraction (MAE). After the extraction, sample purification (generally by SPE) and concentration is advised. •Assessment of PACs in environmental particulate samples is toxicologically relevant.•Active sampling on quartz filters is the most current PM sampling method.•The major extraction methods for PACs in particulates are PLE, UAE and MAE.•Depending on the sample complexity, an extensive clean-up should be considered.